The mansio in Pisidia's Döşeme Boğazı: a unique building in Roman Asia Minor. (2020) - Mitchell, Stephen
Abstract : The Döşeme Boğazı ('Pass with the Pavement') is one of the ancient routes through the Taurus Mountains that connected the Anatolian interior with the southern coastal regions (fig. 1). From an early date it was an important component of the Roman road-system in Asia Minor (fig. 2). The pass lay near the S end of the Republican route from the Dardanelles to Side which was created by Manius Aquillius, first proconsul of Asia between 129 and 126 B.C. The S part of this road was incorporated into the via Sebaste, built in 6/5 B.C., which linked several of the Roman colonies founded by Augustus in south-central Anatolia to the Mediterranean coast. By good fortune, the ancient settlements and the Roman and post-Roman road in this defile have survived largely untouched by modern development. The course of the road between the Roman colony of Comama (Pisidia) and Perge (Pamphylia), as well as branch roads leading to other settlements, can be traced precisely. Well-preserved remains of two settlements, both occupied between the 2nd and 6th c., are identifiable at the upper and lower ends of the defile: in them are houses having from 2 to 10 rooms, the larger ones arranged around courtyards and some having cisterns and towers ( Turmgehöfte ), a bath-house and public cisterns, roadside shops, sarcophagi and small heroa in prominent positions by the road, and numerous churches. The lower site includes a large walled structure probably of the 6th c., that was almost certainly designed as an animal enclosure to control transhumant flocks. Most remarkable of all the surviving structures in the pass, however, are the remains of a mansio or way-station, which survives up to roof level and is the best-preserved building of this type in the entire empire.